Izikhothane youth phenomenon: the Janus face of contemporary culture in South Africa. Issue 2 (3rd April 2017) - Mchunu, K.
Abstract: Izikhothane, is an urban youth phenomenon that has taken some of South African Townships involving the preoccupation with extreme forms of materialism; fatalistic obsession with fashionable clothing brands and expensive alcohol. Local popular music provides the soundtrack. The paper aims to shed light and contribute to discussions about the evolving nature of South African culture concerning youth. It is informed by a constructivist paradigm according to which knowledge is self-constructed. The argument presented is that this youth phenomenon should be understood in the context of a state of flux in contemporary South African society and culture, spiritual malaise and anomie, and commodification, all of which have given rise to a sense of nihilism. The pervasive sense of superfluity belies the bleak economic background of the majority of the youth. The concept of black urbanism provides a different framework for theorizing this subculture as a black experience and phenomenon.